Improving utilisation of industrialised building system (IBS) in low cost housing projects - Kasim, Narimah (2015)
Housing in Malaysia needs to be expedited for sustainable growth as part of economic and social activities. The demand in low cost housing keeps on increasing especially in urban area. The implementation of Industrial Building System (IBS) in low cost housing is desired, however there is lack of incentives and awareness from government in improving IBS implementation in low cost housing projects. The objectives of this research were to investigate the current use of IBS in low cost housing projects, to identify the challenges of IBS usage in low cost housing and to recommend ways for enhancing IBS usage in low cost housing projects. The quantitative approach was used to gain information from contractors (G7) in utilisation of IBS in low cost housing projects. The data gathered was analysed into the form of percentage, tables, and charts by using SPSS software. Successful and effective implementation of IBS in the Malaysian construction industry can offer various benefits compare to conventional systems. Client with a good knowledge and awareness of IBS benefit will surely encourage appointed designers to design building according to IBS specification. These benefits are very important aspects in achieving the efficient and effective which will enhance the market share of construction industry as well as contributing to the Malaysian economy